GUIDING PRINCIPLES ON DISPLACEMENT: INSTITUTIONALISASI NILAI-NILAI KEMANUSIAAN DALAM INSTRUMEN INTERNASIONAL - Sigit Riyanto (Fakultas Hukum Universitas Gadjah Mada, 2008)
This paper examined the process and prospect of the institutionalization of humanitarian values in the international instrument adopted by the United Nations in 1998. As a matter of fact, since the adoption by the United Nations in 1998, this instrument has been disseminated widely and, has been used by various international organisations (both UN Agencies and non UN Agencies), regional organisations, state and non-state entities as guidance in dealing with the internal displacement crisis. Some states even incorporated the principles embodied in this instrument into their national legislation. It has to be noted that The Guiding Principles on Internal Displacement clarify any grey areas that might exist, and address the gaps identified in the existing international legal system. Accordingly, this instrument should be treated as common platform for international community in the efforth of protecting and assisting internally displaced persons throughout the world.